The Terrible Twins - Jepson, Edgar, 1863-1938; Booth, Hanson, 1885-1944 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Terrible Twins" by Edgar Jepson is a children$1 (Bs novel written in the early 20th century. The story follows the adventurous and mischievous twins, Violet Anastasia and Hyacinth Wolfram Dangerfield, who engage in various escapades, including their determination to establish a cats$1 (Bhome. Their antics stem from a desire for independence and self-sufficiency while dealing with the possible intrusion of a suitor to their mother, adding a layer of family dynamics to their playful adventures. At the start of the story, the Twins are introduced as spirited and competitive, particularly in their ability to throw stones, a skill they have honed. They enjoy a spirited debate about their triumphs and grievances against their elders, particularly over being restricted from using catapults. The opening captures their playful rivalry, setting the tone for their relationship with peers like Wiggins. The subplot of the looming marriage proposal from Captain Baster adds tension, prompting the Twins to devise mischievous plans to protect their mother while embarking on their mission to create a cats$1 (Bhome, leading to larger themes of childhood independence, creativity, and the complexities of family and friendship. (This is an automatically generated summary.)s
Release date is 2006-08-14
Al Haines
Keywords: Twins -- Fiction